P5.31 CENTRAL PRESSURES ARE HIGHER IN PATIENTS WITH TRANSIENT ISCHAEMIC ATTACK (TIA) THAN HEALTHY ADULTS - S.R.U. Patel; E. Bunting; E. Bodenham; S.A. Hopkins; E. Ormerod; J. Timeyin; K. Ali; C. Rajkumar (Artery Research, 2013)
Introduction: The increased risk of stroke following a Transient Ischaemic Attack (TIA) is well established. Central aortic pressure, a marker of arterial stiffness, is emerging as a predictor of cardiovascular events including stroke. Additionally brachial Blood Pressure (BP) measurements may not accurately reflect the haemodynamic status of an individual, as systolic BP is amplified peripherally. The association and interplay of central aortic pressure and brachial BP parameters in TIA patients have not previously been explored. Methods: Twenty-six participants with a mean age of 70 years (SD±10.1) and a confirmed diagnosis of TIA were recruited from Brighton and Sussex University Hospitals Trust. Central aortic BP and brachial BP were measured using Arteriograph®. Carotid-femoral pulse wave velocity (C-F PWV) and carotid-radial pulse wave velocity (C-R PWV) were measured using Complior®. Results: Twenty participants had complete BP recordings. Central aortic BP was higher than peripheral BP (mean difference= 2 mmHg). Healthy patients are expected to have a central BP 10–15mmHg lower than peripheral BP.[1,2] C-F PWV was found to be higher in TIA participants compared to published normal values (C-F 10.9 m/s).[3]